2019
DOI: 10.3390/cells8020197
|View full text |Cite
|
Sign up to set email alerts
|

AQP1 and AQP4 Contribution to Cerebrospinal Fluid Homeostasis

Abstract: Aquaporin 1 (AQP1), expressed in epithelial cells of the choroid plexus, and aquaporin 4 (AQP4) present in ependymal cells and glia limitants have been proposed to play a significant role in cerebrospinal fluid (CSF) production and homeostasis. However, the specific contribution of each water channel to these functions remains unknown, being a subject of debate during the last years. Here, we analyzed in detail how AQP1 and AQP4 participate in different aspects of the CSF homeostasis such as the load and drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 45 publications
4
45
2
Order By: Relevance
“…These observations also add to the experimental evidence suggesting that spinal cord formation of water adds to the CSF in supine subjects. Animal studies show that the water channel aquaporin-4 (AQP4), mediating a significant net extra-choroidal formation of CSF water, is abundant in brain and particularly the spinal cord tissue [ 41 ], where perivascular spaces communicate directly with subarachnoid CSF [ 42 , 43 ]. High rates of CSF secretion was previously shown from spinal cord ependyma [ 44 ], and a more recent study showed perivascular outflow of CSF from the entire spinal cord [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations also add to the experimental evidence suggesting that spinal cord formation of water adds to the CSF in supine subjects. Animal studies show that the water channel aquaporin-4 (AQP4), mediating a significant net extra-choroidal formation of CSF water, is abundant in brain and particularly the spinal cord tissue [ 41 ], where perivascular spaces communicate directly with subarachnoid CSF [ 42 , 43 ]. High rates of CSF secretion was previously shown from spinal cord ependyma [ 44 ], and a more recent study showed perivascular outflow of CSF from the entire spinal cord [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since we have observed that cpLECs may anatomically have greater access to the subarachnoid space than the other lymphatics, we next looked to see if they express any water transport proteins that might facilitate sampling of CSF. Aquaporins (AQPs) are often implicated in regulating fluid dynamics, with AQP-1 and AQP-4 most highly expressed in the CNS 41,42 . AQP-4 is expressed by astrocytic endfeet, hypothesized to regulate glymphatic function 43,44,45 , while AQP-1 is expressed on the apical membrane of the choroid plexus and is believed to be involved in CSF production 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Aquaporins (AQPs) are often implicated in regulating fluid dynamics, with AQP-1 and AQP-4 most highly expressed in the CNS 41,42 . AQP-4 is expressed by astrocytic endfeet, hypothesized to regulate glymphatic function 43,44,45 , while AQP-1 is expressed on the apical membrane of the choroid plexus and is believed to be involved in CSF production 43 . Interestingly, a recent study by Norwood et al reported expression of AQP-1 near the cribriform plate, although the identity of the cell types that expressed AQP-1 was unknown 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Choroidal and extrachoroidal CSF production/drainage, at least in experimental conditions, depend on aquaporin-1 and aquaporin-4 water channels, respectively (53,54). Here, we studied the expression patterns and intensities of aquaporin-1 in choroid plexuses as a read-out for putative alterations in choroid plexus functionality and CSF production.…”
Section: Discussionmentioning
confidence: 99%